The THE EFFECT OF REALISTIC MATHEMATICS LEARNING APPROACH ON CONCEPT UNDERSTANDING - Teguh Santoso Teguh; Siti Wulan Purnawati; Eko Yulio Susanto (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2021)
Students' understanding of concepts in mathematics learning is still having difficulties. The purpose of this study was to determine the effect of a realistic mathematics approach on students' understanding of the SPLDV concept. This research is experimental research with one group pretest-posttest design. The place where this research was carried out was SMP Bahrul Maghfiroh Malang. The data collection technique used in this study was a written test. The data analysis technique used is quantitative analysis, namely using descriptive statistics and inferential statistics. The results obtained from the calculation of the hypothesis test Z count> Z table, namely (16,733> 1,645), it can be concluded that H_0 is rejected and H_a is accepted, so that there is a better effect of learning with a realistic mathematics approach in improving students' understanding of the SPLDV concept. Students look more relaxed in participating in learning.